Cognitive and Emotional Drivers of Online Purchase Decisions in Live-Streaming Social Commerce - Lailatul Rohmah (International Journal of Economics, Science, and Education, 2025)
Purpose:This study examines how various internal and external factors influence consumer behavior in the purchase decision-making process by synthesizing findings from previous empirical and theoretical studies. Design/methodology/approach:This study adopts a literature review approach by systematically collecting and analyzing peer-reviewed journal articles and relevant academic sources related to consumer behavior and purchase decision-making. The selected studies were categorized and interpreted based on key determinants such as psychological, social, cultural, and technological factors. Findings: The findings indicate that purchase decisions are shaped by the interaction of cognitive factors (such as perception, motivation, and attitudes) and external influences (such as social environment, marketing stimuli, and digital platforms). Recent literature also highlights the growing importance of online information, social media, and electronic word-of-mouth in accelerating and modifying consumer decision processes. Research limitations/implications:This study is limited to secondary data obtained from published literature, which may restrict the depth of contextual analysis and empirical validation. In addition, variations in research settings and methodologies across reviewed studies may affect the comparability of findings. Practical implications: The results suggest that firms should design marketing strategies that integrate both rational appeals (product information and value propositions) and emotional engagement (brand image and social influence) to effectively influence consumer purchase decisions. Originality/value:This study provides a comprehensive synthesis of cognitive, emotional, and social perspectives on consumer purchase decision-making, offering an integrative framework that can serve as a foundation for future empirical research. Paper type: Literature review